Development of a Rapid and Cost-Effective Method for Estimating Plant Glucose Levels with a Glucometer - Mishra, Akshya Kumar (International Journal of Environment, Agriculture and Biotechnology, 2024)
This work offers a unique glucometer procedure for quick and economical plant glucose determination. The effectiveness of the devised method was demonstrated by its successful application to a variety of plant samples. Tagetes erecta showed the greatest glucose content among the plants studied, while Aegle marmelos showed the lowest. This novel method of measuring plant glucose levels is quicker and less expensive than existing approaches, which gives it a major advantage over others. This approach has the potential to be an effective tool in a number of disciplines, such as agricultural science, ecological research, and plant physiology.